Navigating service variability: A managerial perspective on brand trust in internship-based service SMEs - Sirodjudin, Mochamad; Sudarmiatin, Sudarmiatin; Hermawan, Agus; Rahayu, Wening Patmi (Edelweiss Applied Science and Technology, 2026)
Service-based small and medium-sized enterprises (SMEs) rely heavily on human interaction, making brand trust particularly vulnerable to service variability. This challenge becomes more pronounced when SMEs involve internship-based personnel in service delivery. Although internships are commonly used to support operational flexibility, limited attention has been given to how such practices shape brand trust from a managerial perspective. This study explores how service SMEs manage brand trust under an internship-based service experience. Using a qualitative interpretative approach, data were collected through in-depth interviews, observations, and document analysis involving SME owners, employees, customers, interns, and supporting stakeholders. The findings indicate that brand trust is not automatically weakened by internship involvement. Instead, trust is gradually constructed through managerial supervision, informal service standardization, interpersonal interaction, and stakeholder coordination. Internship-based service experience functions as a trust-sensitive context in which managerial practices determine whether trust is reinforced or undermined. This study contributes to service marketing literature by shifting attention from trust outcomes to managerial processes in resource-constrained SMEs. The findings provide actionable insights for managing internship-based service delivery to sustain brand trust and enhance competitive sustainability.